The Fc gamma receptor IIa R131H polymorphism is associated with inhibitor development in severe hemophilia A. (16th July 2014) - Eckhardt, C. L.; Astermark, J.; Nagelkerke, S. Q.; Geissler, J.; Tanck, M. W. T.; Peters, M.; Fijnvandraat, K.; Kuijpers, T. W.
Summary Background The development of factor (F) VIII neutralizing alloantibodies (inhibitors) is a major complication of treatment with FVIII concentrates in hemophilia A and the etiology is still poorly understood. The low‐affinity Fc gamma receptors (FcγR), which are expressed on immune cells, provide an important link between cellular and humoral immunity by interacting with IgG subtypes. Genetic variations of the genes encoding FcγRs (FCGR genes) have been associated with susceptibility to infectious and autoimmune diseases. Objectives The aim of this study was to investigate the association between genetic variation of FCGR and inhibitor development in severe hemophilia A. Patients/Methods In this case‐control study samples of 85 severe hemophilia A patients (siblings from 44 families) were included. Single nucleotide polymorphisms and copy number variation of the FCGR2 and FCGR3 gene cluster were studied in an FCGR‐specific multiplex ligation‐dependent probe amplification assay. Frequencies were compared in a generalized estimating equation regression model. Results Thirty‐six patients (42%) had a positive history of inhibitor development. The polymorphism 131R > H in the FCGR2A gene was associated with an increased risk of inhibitor development (odds ratio [OR] per H‐allele, 1.8; 95% confidence interval [CI], 1.1–2.9). This association persisted in 29 patients with high titer inhibitors (OR per H‐allele, 1.9; 95% CI, 1.2–3.2) and in 44 patients with the F8 intron 22 inversion (OR per H‐allele, 2.6; 95% CI, 1.1–6.6). Conclusions Hemophilia A patients with the HH genotype of the FCGR2A polymorphism 131R > H have a more than 3‐fold increased risk of inhibitor development compared with patients with the RR genotype.